Ethics in a multicultural context - Pack-Brown, Sherlon P. (Multicultural aspects of counseling and psychotherapy., 2003)
Ethics in a Multicultural Context provides strategies for critical decision making in multicultural settings. Utilizing extensive case studies, authors Sherlon P. Pack-Brown and Carmen Braun Williams present a comprehensive exploration of counseling ethics in a cultural context. Examining the implications and consequences of competent multicultural counseling, they present ethical dilemmas arising in face-to-face counseling interactions, supervisory relationships, and educational situations. This book encourages critical thinking rather than passive acceptance.